A Correlation between the Activeness of the Elderly in Participating in Posyandu Activities with the Quality of Life in the Area of Batu Bandung Health Center in 2024 - Rahayu, Pupu Yuni; Hilianti, Yatri; Lestari Nurjanah, Nimas Ayu (Student Scientific Journal, 2025)
Aging is a natural process that everyone cannot avoid. An old person will experience physical and behavioral changes that occur when someone reaches a certain chronological stage of development. Elderly health is currently an important issue in the health sector. The aging process brings changes in various aspects, including social, psychological, and physical, which are influenced by degenerative processes. Therefore, the existence of elderly health posts is very important to improve the quality of life of the elderly. The goal is for the elderly to remain healthy, independent, and productive socially and economically. This research is a quantitative study, using an observational analytical research type with a cross-sectional approach. This research was conducted in the working area of Batu Bandung Public Health Center which was carried out in July 2024. The number of samples in this study was 32 old people age 65-70 years. From the results of the statistical test, a p-value of 0.006 was obtained, which means that there is a relationship between the activeness of the elderly in attending integrated health posts and the quality of life of the elderly with an OR value of 11.3. It is hoped that health center officers will provide counseling and socialization on the importance of the elderly integrated health post among the community so that elderly visits to the integrated health post are maximized in order to improve the quality of life of the elderly in living their old age.